Analisis kebutuhan modul matematika untuk meningkatkan kemampuan pemecahan masalah siswa SMP kelas VII - Annisa Sulistyaningsih; Suparman Suparman; Ellya Rakhmawati; Surasmanto Surasmanto (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2019)
The 21st century learning process requires effective and innovative teaching materials. One teaching material that can help smooth the teaching and learning process in schools is a module. This study has two objectives. The first objective is to analyze the needs of mathematics textbooks that can improve students' problem solving abilities in accordance with the Problem Based Learning (PBL) model. The second objective is to identify learning problems faced by students and analyze the suitability of textbooks with SILABUS. This study uses descriptive qualitative. The research subjects were mathematics lesson teachers and seventh-grade students of SMP Negeri 09 Yogyakarta. Data on learning resources are collected by interviewing mathematics teachers. Data on students' problem solving abilities were collected by observation on class VII students. Data analysis techniques using data reduction, data presentation, and conclusion. This study has two results. The first result is the textbook used is not in accordance with core competencies, not in accordance with basic competencies, not in accordance with indicators of achievement of competence, and the existing questions are considered difficult by students. The second result is the absence of learning models applied in textbooks. So that a textbook is needed in the form of modules that can improve problem solving skills in students with PBL models; Teachers and students state that needing textbooks in the form of mathematical modules that can be understood, motivated in learning, there are many models of questions that are real so students agree and support the creation and development of mathematical modules to improve problem solving skills.Keywords: needs analysis; mathematics module; problem solving ability; problem based learning.